Mediating brand trust, brand attitude, and brand psychological ownership on celebrity endorsers to behavioural intention - Elsi Safira; Indah Fatmawati; Nuryakin Nuryakin (Jurnal Fokus Manajemen Bisnis, 2023)
The marketing type that is found on social media today is celebrity endorsement. To encourage consumer behavioural intention, luxury brand companies take several strategies, including using celebrity endorsers to introduce their brand and to build brand trust, brand attitude, and brand psychological ownership. This study aims to examine the influence of celebrity endorsers on behavioural intention through the mediation of brand trust, attitude, and psychological ownership. A total of 250 samples were determined by purposive sampling. This research used a quantitative approach and structural equation modelling (SEM) AMOS as a data analysis technique. The result showed a mediating effect of brand trust, attitude, and psychological ownership on the relationship between celebrity endorsers and behavioural intention.